Subhashitavali - Haksar, A.N.D (New Delhi, 2007)
The subhashita verse is a popular feature of Sanskrit literature. Composed in isolation or as part of a larger work, it is essentially a miniature poem which encapsulates a complete thought, mood or image in a single stanza.
Keywords: English poetry; IFS as an Translator